2020
DOI: 10.1002/mus.27115
|View full text |Cite
|
Sign up to set email alerts
|

Nodal conduction block: A unifying concept

Abstract: A newly introduced term, “axonal conduction block,” brought a confusion in the electrodiagnostic diagnosis of Guillain‐Barrè syndrome (GBS). I am proposing the term “nodal conduction block” for “axonal conduction block.” This unifying concept of nodal conduction block will accommodate both the traditional concept of demyelination as well as the new concept of nodopathy in the “axonal form of GBS,”, making the practice of electrodiagnosis much easier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…If an autoimmune attack is aborted, axonal degeneration does not progress and nodal function rapidly recovers, which represents the pathomechanism of RCF 12,13 . RCF in AMAN has been considered a sign of nodopathy and has a favorable prognosis 14 . Many previous reports have suggested that AMAN without RCF has the worst prognosis in GBS 15,16 , similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…If an autoimmune attack is aborted, axonal degeneration does not progress and nodal function rapidly recovers, which represents the pathomechanism of RCF 12,13 . RCF in AMAN has been considered a sign of nodopathy and has a favorable prognosis 14 . Many previous reports have suggested that AMAN without RCF has the worst prognosis in GBS 15,16 , similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…If an autoimmune attack is aborted, axonal degeneration does not progress and nodal function rapidly recovers, which represents the pathomechanism of RCF [22,23] . RCF in AMAN has been considered a sign of nodopathy and has a favorable prognosis [24] . Many previous reports have suggested that AMAN without RCF has the worst prognosis in GBS [10,13] , similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent understanding of the pathogenesis of immune-mediated neuropathies has highlighted a need for more systematic classification ( 4 , 10 , 11 ). Nerve biopsy is not recommended as a routine diagnostic procedure due to its infeasibility and morbidity ( 5 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of electrodiagnosis (EDX) is even more limited, as nodo-paranodopathy exhibits significant overlap with classical axonopathies or demyelinating neuropathies in terms of electrophysiological changes. Dysfunction of voltage-gated sodium channels at the node of Ranvier may delay the generation of action potentials leading to significant conduction slowing into the “demyelinating range” ( 10 , 11 , 19 ). Where axonal degeneration may follow nodal immune attack, EDX of nodo-paranodopathy can mimic that of classical axonopathy.…”
Section: Introductionmentioning
confidence: 99%